MANAJEMEN PELAYANAN SOSIAL: Peran Pusat Dukungan Anak Dan Keluarga di Panti Asuhan Yogyakarta - Dwi Papsa (UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to determine how the role played by the Sayangi Tunas Cilik Foundation Partner of Save the Children Pusat Dukungan Anak dan Keluarga (PDAK) program in building social service management in Yogyakarta orphanages. The results showed that there were several roles, namely the facilitative role through the socialization of the application of the National Childcare Standards (SNPA), the educational role through training in the form of workshops and capacity building in case counseling, the role of representatives through PDAK efforts in assisting the completeness of LKSA accreditation administration and the technical role through data processing training with a case management approach. The results of the role of building service management include understanding and developing LKSA's capabilities in family-based care, implementing case management, and acknowledging LKSA through accreditation. All the assistance roles carried out by PDAK are to increase family-based care and instill a culture of good parenting, and to support the recognition of the LKSA service system through LKSA accreditation.Keywords: Role of PDAK, management of social services, children and families